Relationship through a screen: a systematic review and meta-analysis on therapeutic alliance, client and therapist perceptions, and the mode of psychotherapy - Lim, Ziyun (Nanyang Technological University, 2022)
In light of the COVID-19 pandemic, there has been an increasing prevalence of telehealth use, particularly in telemental health. However, there have been mixed findings regarding the therapeutic alliance, as well as the client’s and therapist’s perceptions of telepsychotherapy. Therefore, this combined meta-analysis and systematic review paper aims to further explore the relationship between client and therapist-rated therapeutic alliance and the modes of psychotherapy, as well as the relationship between clients’ and therapists’ perceptions of therapy and modes of psychotherapy. Twenty-one effect sizes from 14 studies (11 quantitative, three qualitative) comprising 641 participants were analysed in the current study. Overall, a significant and negative combined effect size was found between client ratings of therapeutic alliance and the mode of psychotherapy, where the use of telepsychotherapy negatively affected clients’ mean therapeutic alliance scores. Through moderation analyses, there were no significant moderation effects of (a) type of psychotherapy, (b) sample size, (c) number of sessions, (d) mean age of participants and (e) duration of each therapy session. Client perceptions of therapy were not significantly different between online and offline modes of psychotherapy, and in the transition to telepsychotherapy, therapists tend to perceive and experience more difficulties in practice. Client perceptions of therapeutic alliance and telepsychotherapy were found to improve across treatment duration. The limitations of the present study and implications for future research are also discussed.